2005
DOI: 10.1063/1.1931824
|View full text |Cite
|
Sign up to set email alerts
|

Stability of phase-modulated quantum key distribution systems

Abstract: Phase drift and random fluctuation of interference visibility in double unbalanced M-Z QKD system are observed and distinguished. It has been found that the interference visibilities are influenced deeply by the disturbance of transmission fiber. Theory analysis shows that the fluctuation is derived from the envioronmental disturbance on polarization characteristic of fiber, especially including transmission fiber. Finally, stability conditions of one-way anti-disturbed M-Z QKD system are given out, which prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…These results suggest that our PLC-based interferometer allows us to implement a QKD system insensitive to polarization effects that may occur in the transmission fiber, since the same balancing condition is sufficient to achieve polarization insensitivity [38]. The polarization-insensitive operation of a time-division interferometer based on our PLC AMZI has actually been proven by the authors using the experimental setup shown in Figure 7 [35,36].…”
mentioning
confidence: 81%
“…These results suggest that our PLC-based interferometer allows us to implement a QKD system insensitive to polarization effects that may occur in the transmission fiber, since the same balancing condition is sufficient to achieve polarization insensitivity [38]. The polarization-insensitive operation of a time-division interferometer based on our PLC AMZI has actually been proven by the authors using the experimental setup shown in Figure 7 [35,36].…”
mentioning
confidence: 81%
“…Nevertheless in a real station node, it is not convenient to plug such a device into the well-compacted system box. Significantly, FMI QKD set-up can take advantage of the Faraday mirrors to constrain the influence of the polarization in the way [7,18] . A Faraday mirror's Jones matrix can be given as 0…”
Section: Basic Qkd-link Devicementioning
confidence: 99%
“…In 2005, Lo, Chau and Ardehali [9] proposed an asymmetrical BB84 protocol which has a higher efficiency than the original BB84 protocol. Phase-coding quantum cryptography protocols [15][16][17][18][19] have been proposed for overcoming the birefringence of an optical fiber. With a private key, Alice and Bob can transmit their secret message securely with the Vernam one-time pad crypto-system.…”
Section: Introductionmentioning
confidence: 99%